Cristianismo en la sociedad indígena costarricense, siglos XVI a XVII - Alvarado Quesada, Franklin José (1996)
A study of the missionary and evangelizing methods, types of preaching sacraments and other religious expressions of Franciscan religious projection from 1563 and 1689.